2015
DOI: 10.1007/s13178-015-0197-6
|View full text |Cite
|
Sign up to set email alerts
|

Homonegativity in Italy: Cultural Issues, Personality Characteristics, and Demographic Correlates with Negative Attitudes Toward Lesbians and Gay Men

Abstract: This study is an extension of earlier research that\ud investigated the nature of homonegativity among Italian people\ud (Lingiardi et al. 2005).We used the Modern Homophobia\ud Scale (MHS), adapted to be more appropriate for the Italian\ud social and cultural context. Associations were examined between\ud homophobic attitudes, demographics, and personality\ud characteristics and contact with lesbians and gay men. Gender\ud issues were considered twice, from the viewpoint of both the\ud agent and the target of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
77
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 99 publications
11
77
0
6
Order By: Relevance
“…This seems to be in line with the current Italian situation where the attempts to expand civil rights to homosexual couples and families still clash with the outcries of political sections strongly influenced by the Catholic Church [75]. Furthermore, it is interesting that in MtFs internalized transphobia was significantly highest according to levels of religious fundamentalism.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This seems to be in line with the current Italian situation where the attempts to expand civil rights to homosexual couples and families still clash with the outcries of political sections strongly influenced by the Catholic Church [75]. Furthermore, it is interesting that in MtFs internalized transphobia was significantly highest according to levels of religious fundamentalism.…”
Section: Discussionsupporting
confidence: 76%
“…The different figure observed in the present study may be the consequence of not conforming to social expectations related to the female gender role of lesbian women. These are of relevance in a heteronormative and familybased culture such as the Italian context [75].…”
Section: Discussionmentioning
confidence: 99%
“…Ehrensaft's (2000) clinical observations with female-partnered mothers via assisted reproduction are also considered. In keeping with previous qualitative studies on the same topic (Goldberg et al, 2012;, social constructionism sheds light on how female-partnered mothers' personal interpretations of their sperm donor are influenced by their relationship with the partner and the child, as well as by the broader, dominant, Italian heteronormative discourses (Lingiardi et al, 2016) regarding same-sex parenthood and access to assisted reproduction. This study further draws on the intersectionality paradigm (Cole, 2009), as it accounts for how women's multiple identities may intersect to influence their thoughts, feelings and images of the donor at two or more axes of experience -here, being the biological or the non-biological mother, pursuing an anonymous or an open-identity donor, and transnational donation.…”
Section: Comment [Cf1]supporting
confidence: 56%
“…Despite the legal vacuum and the homophobic stigma (Baiocco et al, 2015;Lingiardi et al, 2016), an increasing number of gay men and lesbian women are becoming parents (Baiocco and Laghi, 2013;Baiocco et al, 2014). When lesbian women decide to have children within their current relationship, they have to turn to third-party reproduction offering a spectrum of possibilities regarding both donor arrangement (from open-identity to anonymous) and degrees of familiarity with the donor (from family members to strangers living in other countries).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, our findings suggest that bullying experiences may heighten the vulnerability of SMM, with consequences for basic health behaviors. This finding for SMM was not present in the New York City sample (Thapa & Kelvin, ); other studies have shown that sexual minority youth (Kosciw et al, ), especially males (Lingiardi et al, ), may be more vulnerable in socially conservative settings.…”
Section: Discussionmentioning
confidence: 60%